Life cycle exposure to 2-phenylbenzimidazole-5-sulfonic acid disrupts reproductive endocrine system and induces transgenerational adverse effects in zebrafish - Tao, Junyan; Yang, Qinyuan; Sun, Xiaowei; Tian, Linxuan; Deng, Yuanzhi; Wang, Yumei; Wang, Weiwei; Fan, Xiaoming (Frontiers in Marine Science, 2023)
Global attention has been focused on organic UV filters due to their ubiquity and potential damage to aquatic environment, yet the effects of their life cycle exposure on fish reproduction remain unknown. In the present study, the influence of 2-phenylbenzimidazole-5-sulfonic acid (PBSA) exposure on the reproductive endocrine system of zebrafish was examined, from 6 hours post fertilization (hpf) until 150 days, at levels that near-environmentally relevant (0 to 20 μg/L). Our results showed that exposure to PBSA at 20 μg/L caused a slight decrease in the Gonadosomatic Index (GSI) of female zebrafish in the F0 generation. Furthermore, this exposure had a negatively effect on reproduction, accompanied by delayed oocyte maturation, reduced cumulative egg production and decreased fertilization rate. Additionally, offspring embryos displayed reduced egg diameter at 0.75 hpf, delayed cumulative hatching rate at 60 hpf, and increased deformities rate at 72 hpf, indicating an adverse transgenerational effect. Moreover, PBSA exposure was associated with decreased plasma levels of sex hormones of 17β-estradiol (E2) and 11-ketotestosterone (11-KT), as well as altered the transcriptional profiles of certain genes in the HPG (hypothalamic–pituitary–gonadal) and liver axis. Molecular docking (MD) simulations revealed that specific amino acid residues of PBSA interact with zebrafish estrogen receptors, confirming its xenoestrogenic properties. Therefore, exposure to PBSA during its life cycle can disturb fish reproduction through endocrine disruption, thus necessitating strict environmental regulations for the disposal of UV filters to protect ecological and public health.